Investigating Online Quran Interpretation: Methods and Sources on Muslimah.or.id and its Contribution to Online Islamic Discourse - Rahmawati, Dewi; Abouzeid, Mohamed Sharei; Nirwana AN, Andri; Hidayat, Syamsul; Rhain, Ainur (QiST: Journal of Quran and Tafseer Studies, 2025)
Technological advancements are increasingly shaping daily life. This includes the dissemination of information, with Muslims utilizing technology for Islamic da'wah, particularly Qur'anic interpretation (Tafsīr). While traditionally accessed through physical prints, Tafsīr is now readily available on websites. This study analyzes the sources, methods, and patterns of interpretation employed by http://muslimah.or.id. Employing a qualitative research method with a descriptive-qualitative approach, the study reveals several key features of the website's Tafsīr approach. Interpretations focus on individual letters, specific themes, and contemporary Muslim women's issues. Authors cite reference sources, and interpretations are diverse, reflecting at least four distinct methods. The website incorporates both traditional (bi al-Maʼthūr) and rational (bi al-Ra'y) methods, drawing from classical Tafsīr works like Jalalain, at-Ṭabarī, and Ibn Kathīr. Notably, the website utilizes thematic (Mawḍūʻī) and comparative (Muqāran) approaches. The website prioritizes socio-literary (Adabī ijtimāʻī) aspects, focusing on linguistic, literary, and socio-cultural contexts. However, the inconsistent nature of interpretations due to the website's multiple contributors presents a potential challenge.